The Criteria for Evaluating and Selecting Mobile Applications for Diabetes Care - Dr. Zohair Jamil Gazzaz, Dr. Mohammed Khursheed Akhtar (International Journal of Advanced Science and Technology, 2020)
It has been known since long time that diabetes is painstaking and as serious disease. If it is not controlled in time, it will be very fatal. Most of the healthcare institutions are using ordinary application for diagnosis and reporting purposes for Diabetes Mellitus (DM). In this era of advanced technology, the diabetes diagnosis and reporting are better represent and easily manage and track the trend with the fingertips access. In this paper, the aim of our study was to evaluate and select the suitable existing mobile application using specific criteria, which will help us to diagnose, maintain, control and monitor the DM level.